2018
DOI: 10.1142/s0218539318500183
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Reliability-Optimal Release Time of Software with Patching Considered

Abstract: Testing life cycle poses a problem of achieving a high level of software reliability while achieving an optimal release time for the software. To enhance the reliability of the software, retain the market potential for the software and reduce the testing cost, the enterprise needs to know when to release the software and when to stop testing. To achieve this, enterprises usually release their product earlier in market and then release patches subsequently. Software patching is a process through which enterpris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…This phenomenon suggested that release and testing stop time should be different. Few recent studies (Jiang et al , 2012; Kapur and Shrivastava, 2015; Anand et al , 2017; Kapur et al , 2017; Kumar et al , 2018) used this idea to propose a new framework for developing a cost model to determine separate release and testing stop time. But all these studies were having strong assumptions of perfect debugging and with no change point that seems unrealistic in practicality.…”
Section: Conclusion Managerial Implication and Further Area Of Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon suggested that release and testing stop time should be different. Few recent studies (Jiang et al , 2012; Kapur and Shrivastava, 2015; Anand et al , 2017; Kapur et al , 2017; Kumar et al , 2018) used this idea to propose a new framework for developing a cost model to determine separate release and testing stop time. But all these studies were having strong assumptions of perfect debugging and with no change point that seems unrealistic in practicality.…”
Section: Conclusion Managerial Implication and Further Area Of Researchmentioning
confidence: 99%
“…Sachdeva et al (2018b) proposed a cost framework to separately optimize both times to stop testing and release time of software under warranty by assuming that testing continues beyond software release time. Kumar et al (2018) proposed a cost and reliability-based model to optimize the release and testing stop time. Anand et al (2019) proposed a framework to determine the software-patching schedule.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed a scheduling policy for a software product and showed the importance of patching in lowering the system outages and making the system more cost effective. Kumar et al [24] discussed the reliability, which is a major attribute of the quality of a software, to address the issues of testing cost, release time of software, and a desirable reliability level. Kumar et al [24] developed a reliability growth model implementing software patching to make the software system reliable and cost effective.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al [24] discussed the reliability, which is a major attribute of the quality of a software, to address the issues of testing cost, release time of software, and a desirable reliability level. Kumar et al [24] developed a reliability growth model implementing software patching to make the software system reliable and cost effective. Tickoo et al [34] have proposed a testing effort based cost model to determine the optimal release time and patch time of a software.…”
Section: Introductionmentioning
confidence: 99%
“…Though a number of optimal release planning models have been proposed in the literature to determine software release time, very few of them incorporate the effect of warranty on release management (Kapur et al , 2017; Kumar et al , 2018; Okumoto and Goel, 1979). In this paper, we aim to address this research gap.…”
Section: Introductionmentioning
confidence: 99%